Pengaruh Pelatihan Kerja, Kemampuan Teknologi Dan Kompetensi Terhadap Kepuasan Kerja Karyawan PT. Bumi Sarana Utama Cabang Makassar - Muh Rais; Baso Amang; Kasnaeny Kasnaeny (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
ABSTRACT This study aims to determine the effect of Job Training, Technological Capability, and Competence on Employee Job Satisfaction at PT. Bumi Sarana Utama Makassar Branch. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 43 respondents. The sampling technique used is saturated sampling, because the entire population was used as the research sample. The data obtained were analyzed using multiple linear regression with the assistance of the SPSS program. The results of the study show that partially, Job Training has a positive and significant effect on Employee Job Satisfaction, with a t-value of 2.602 and a significance value of 0.013. Technological Capability has a positive and significant effect on Employee Job Satisfaction, with a t-value of 3.237 and a significance value of 0.002. Competence also has a positive and significant effect on Employee Job Satisfaction, with a t-value of 3.531 and a significance value of 0.001. Simultaneously, Job Training, Technological Capability, and Competence have a significant effect on Employee Job Satisfaction, with an F-value of 30.475 and a significance value of 0.000. The coefficient of determination, R Square, of 0.701 indicates that Job Training, Technological Capability, and Competence are able to explain 70.1% of Employee Job Satisfaction, while the remaining 29.9% is explained by other factors outside this study. The most dominant variable influencing Employee Job Satisfaction is Technological Capability, with a Beta value of 0.389. Keywords: Job Training, Technological Capability, Competence, Employee Job Satisfaction.